RETRACTED: Development of algorithms for assessing the regional distribution of respiratory activity parameters based on the analysis of EIT results - Aleksanyan Grayr; Kucher Artyom; Katsupeev Andrey (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001